Direct detection of elephant endotheliotropic herpesvirus 1 (EEHV1) DNA in heparinized plasma by loop-mediated isothermal amplification - TAKEHANA, Kazuya; MATSUNO, Keita (Journal of Veterinary Medical Science, 2023)
Elephant endotheliotropic herpesvirus (EEHV) causes a fatal hemorrhagic disease and is a significant cause of mortality in juvenile Asian elephants. A loop-mediated isothermal amplification (LAMP) method was developed to rapidly diagnose EEHV viremia. However, extracting DNA from whole blood samples to perform LAMP hampers diagnosis in a field setting. Here, we established the Direct-LAMP method, using heparinized plasma without extracting the DNA to speed up and simplify the test. EEHV-positive specimens were tested using the Direct-LAMP. The detection limit was calculated to be 101.3 copies/μL using the mimetic samples, which was almost identical to the value determined in LAMP in which DNA was extracted. Hence, the Direct-LAMP provided a more rapid diagnosis to save, which could prevent elephant deaths.